Analisis Faktor Berbagi Informasi Pribadi di Media Sosial: Studi Skala Kecil - Belia Rida Syifa Fauzia; Lukman Yudokusumo; Yova Ruldeviyani (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2024)
In the contemporary social landscape, the widespread use of social media, such as platforms like TikTok, Instagram, and YouTube, has become a prominent trend in various circles of society, especially in Indonesia. As the number of users on these platforms increases, concerns regarding user security and privacy also increase. Data breaches in 2021 affecting 235 million users on Instagram, TikTok, and YouTube underscored the importance of researching the multifaceted dynamics around privacy concerns, levels of trust, risk awareness, and user behavior patterns related to sharing personal information on social media platforms. This research aimed to address this critical issue by introducing a research model developed based on relevant hypotheses from previous research. The sample used in this research consisted of social media users in Indonesia. Methodologically, this research used sophisticated structural equation modeling (SEM) tools for hypothesis testing and confirmatory factor analysis (CFA) to validate the efficacy of existing research models. These findings indicated that users’ trust, awareness, privacy concerns, and behavioral intentions significantly and positively influence the tendency to share personal data on social media platforms. This research provides valuable insights into the complex interactions between factors influencing user behavior in social media privacy, thereby offering implications for academia and practical applications.